Papillary Endometrial Adenocarcinoma with Cervical Dysplasia: Report of a Case and Review of Literature - Ramezani, Mazaher; Siami, Shadi; Hosseini, Somaye; Sadeghi, Masoud (Asian Pacific Journal of Cancer Biology, 2023)
Objective: Multifocality in gynecologic malignancies is a common phenomenon, however synchronous tumors may occur. Synchronous cancers are about 1.7% of gynecologic malignancies. Methods: A 57-year old female with chief complaint of vaginal bleeding was admitted. Endometrial curettage and cervical biopsy was done. Result: Pathologist reported: compatible with papillary adenocarcinoma, Grade II in endometrial sample and squamous epithelium with moderate dysplasia and tiny fragments of atypical glandular epithelium in endocervical samples. The patient refused for surgical excision of the lesion and insisted on to treat with conventional herbal medicine. Later Pap smear was done and pathologist reported: “High grade squamous intraepithelial lesion (HSIL) and atypical glandular cells, favor neoplastic in atrophic background”. Conclusion: In the case of gynecologic cancer be careful that it may accompany another gynecologic malignancy or premalignant lesion. The second lesion may occur synchronous or metachronous or may be metastatic. Many of the synchronous malignancies are presented in lower stages and have better prognosis than metastatic lesion. Thorough sampling and examination is important in correct diagnosis and treatment.